2017
DOI: 10.4338/aci-2017-04-ra-0059
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Overridden Medication-related Clinical Decision Support in the Intensive Care Unit between a Commercial System and a Legacy System

Abstract: The vendor system had much higher rates of both alerts and overrides, although we did not find evidence of harm in a review of DDIs which were overridden. We propose recommendations for improving our current system which may be helpful to other similar institutions; improving both alert presentation and the underlying knowledge base appear important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 32 publications
0
15
0
1
Order By: Relevance
“…Efforts had been continually made to our legacy system to improve available clinical CDS, including increasing its positive predictive value (PPV) to limit potential alert fatigue 18 19. With the transition to the commercial EHR, we found a significant increase in alerts by approximately five-fold, along with a significant increase in over-ride rates of certain alert types 20. Potential reasons for this significant increase were the removal of our tailored CDS as well as the presentation of CDS alerts at the time of order signing, instead of at the time of ordering as in the legacy system.…”
Section: Discussionmentioning
confidence: 91%
“…Efforts had been continually made to our legacy system to improve available clinical CDS, including increasing its positive predictive value (PPV) to limit potential alert fatigue 18 19. With the transition to the commercial EHR, we found a significant increase in alerts by approximately five-fold, along with a significant increase in over-ride rates of certain alert types 20. Potential reasons for this significant increase were the removal of our tailored CDS as well as the presentation of CDS alerts at the time of order signing, instead of at the time of ordering as in the legacy system.…”
Section: Discussionmentioning
confidence: 91%
“…Other similar systems described by the scientific literature do not include this facility, and the incorporated commercial bundle of CRs cannot be modified by the user. 30,31 Finally, another major benefit of HIGEA is that it was provided with a large set of CRs that covers a wide range of clinical conditions and provides a specific dosage recommendation for the new prescription. 32 Only 10% of published studies in this area 15 use rules that have been defined according to clinical needs.…”
Section: Discussionmentioning
confidence: 99%
“…It has already been demonstrated that an updated and consistent knowledge base positively affects the efficiency of these systems. 31 The "program of dose adjustment in renal impairment" was prioritized because of the high number of drugs that have to be adjusted in patients with renal impairment and the very scant knowledge of these drugs among health professionals. In fact, it has been demonstrated that the rate of appropriate drug prescribing in kidney impairment is low and that the use of a CDSS could improve patient safety.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 While medication-related alerts in clinical decision support systems often lead to alert fatigues, inappropriate alert overrides may post preventable harm to patients. 17,18 An effective way to prevent errors is to learn from patient safety events, including unsafe conditions, near misses and incidents. Many event-reporting systems have been created and put in use for learning purpose, which enables patient safety specialists to analyze events, identify underlying factors, and generate actionable knowledge to mitigate risks.…”
mentioning
confidence: 99%